Safeguarding Financial Stability : Theory and Practice - Schinasi, Garry (International Monetary Fund, 2005)
How is finance related to economic processes, and why should it be viewed as a public good requiring policy action? This book provides an answer. The book develops a practical framework for safeguarding financial stability, which encompasses both prevention and resolution of problems. It also examines on-going and future challenges to financial stability posed by globalization, a growing reliance on derivatives and their markets, and the capital market activities of insurers and reinsurers.